Optimalisasi Kinerja Simpang Tak Bersinyal Berdasarkan Karakteristik Lalu Lintas di Kawasan Jalan Bandulan–Jalan Bandulan Barat–Jalan TPA Supit Urang - Yuliana Ilen Ina Malo; Galih Damar Pandulu; Andy Kristafi Arifianto (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
There is a relatively large volume of traffic at the intersection without traffic lights on Jalan Raya Bandulan, Jalan Barat, and Jalan Bandulan in Sukun District, Malang City. This intersection does not yet have a traffic signal device (APILL). Especially during rush hour, this condition often causes vehicle congestion, which leads to irregular traffic and frequent traffic jams. This study uses a quantitative research design with a descriptive research type. Primary and secondary data are needed for proper data collection. This study aims to determine traffic performance at the intersection of Jalan Raya Bandulan, Jalan Barat, and Jalan Bandulan in Sukun District, Malang City. The results of the performance analysis at the intersection show that vehicle delays are relatively substantial, with congested traffic flow, long queues, and vehicle speeds dropping to less than 30 km/hour. Vehicle speed and volume can decrease to almost zero in some circumstances, especially when there are long queues, even when the reported traffic volume is not too high. This intersection is classified as service level E according to the service level assessment. The average delay per vehicle is 34.85 seconds, indicating that traffic conditions are approaching saturation and require more control.